KEWENANGAN MENTERI DALAM NEGERI DALAM MEMBATALKAN PERDA PROVINSI DAN PERDA KABUPATEN/KOTA Kajian Terhadap Putusan MK Nomor 56/PUU/-XIV/2016 - BAEHAQI, BAEHAQI (Dinamika Hukum, 2018)
The purpose of this study is to analyze The Ministry of Internal Affairs authority to annul The Local Adjustment and The Supreme Court in Judical Review after The Judgement of MK No.56/PUU-XIV/2016 and also to analyze the law strength of The Ministry of Internal Affairs authority to annul The Local Adjusment. Presendece of the judgement, The Constitution Court passed by The Judgement No. 137/PUU-XIII/2015 explain that section 251 of UU No. 23 year 2014 about The local adjusment of the related area with authority to annul the city adjusment no longer could annul by Governor or The Ministry of Internal Affairs. Afterwards, The Supreme Court passed by The Judgement No.56/PUU-XIV/2016 explain The Central Goverment no longer have authority to annul The ProvinceLocal Adjusment. The problems formulation that would be explain in this paper is about how is the authority of annuling The Local Adjusment by The Ministry of Internal Affairs after The JudgementNo. 137/PUU-XIII/2015 and No.56/PUU-XIV/2016. The research method consist of yuridis normatif and the nature of the research isdescriptive research. The materials of the research consist of UU No. 23 year 2014, UU No. 12 year 2011 and The Judgement No. 137/PUU-XIII/2015 and No.56/PUU-XIV/2016. The result of research and the assesment in The Judgement of MK shows that The Ministry of Internal Affairs njo longer have the authority to annul The City/ProvinceLocal Adjusment, therefore the Government which has the higher position could be given an authority to supervise the newborn regulation in the local area. Theimplementation of the supervision can be applied by founding the local area with strengthen the executive preview or testing a law norm before legitimate legally, it is compliance with the sense of UUD NRI 1945section 24A. Keywords : annul, the local adjusment